Analisis Penggunaan Metode Tilawati Dalam Mengoptimalkan Kemampuan Baca Tulis Alquran Pada Siswa Di MI Insan Mulia Tahun Pelajaran 2020/2021 - Amala, Gushaini Ikhsaniafi; Mahrusun, Mahrusun; Dinansyah, Dinansyah (STAI Denpasar Bali, 2021)
The use of methods in learning the Koran is one of the efforts in optimizing the learning of the Koran for students. So the school needs to choose the right method. Which is the selection of the right method can optimize the results of learning to read and write the Koran in students. The purpose of this study was to determine: (1) the ability of students in learning to read and write the Koran at MI Insan Mulia, Jimbaran (2) The application model of the Tilawati method used in an effort to optimize the ability to read and write the Koran in students at MI Insan Mulia, Jimbaran (3) supporting and inhibiting factors while applying the Tilawati method in optimizing learning to read and write the Koran for students at MI Insan Mulia, Jimbaran for the 2020/2021 academic year. This type of research is qualitative. Data collection techniques used in this study were observation, interviews, and documentation. The results of the study revealed that: (1) Students' learning outcomes of the Koran decreased slightly in the odd semester and began to increase in the even semester of the 2020/2021 school year (2) The use of the tilawati method can optimize students' reading and writing skills of the Koran (3) Supporting factors of optimizing learning The Qur'an with the tilawati method at MI Insan Mulia is an adequate Madrasah infrastructure and an effective method. While the inhibiting factor is that some teachers have not been certified as tilawati teachers.